Perception of disease, dyadic coping, and the quality of life of oncology patients in the active treatment phase and their life partners: an approach based on the actor-partner interdependence model - Ştefănuţ, Adelina Mihaela; Vintilă, Mona; Bădău, Larisa Maria; Grujic, Daciana; Oprean, Cristina Marinela; Goian, Cosmin; Sârbescu, Paul (Frontiers in Psychology, 2023)
Objective: The aim of this study based on the Systemic Transactional Model was to examine the relationship between dyadic coping and 1) disease perception and 2) quality of life of a sample of cancer patients and their life partner. Method: This cross-sectional study included 138 oncological dyads. The following questionnaires were used: Stress Appraisal Measure, Dyadic Coping Inventory, and European Organisation for Research and Treatment of Cancer QLQ-C30. Data collected was analysed by applying the actor-partner interdependence model. Results: The perception of the disease as a threat as well as its centrality significantly negatively influences the positive forms of dyadic coping while the perception of the disease as a challenge has a significant positive influence on them. Dyadic coping does not influence symptoms but has significant influences on global health/quality of life. Conclusion: This study has highlighted new information regarding how couples cope with cancer. The results encourage inclusion of perception of the disease and dyadic coping in interventions that aim to improve the quality of life of cancer patients and their life partners.